The preaching community - a practical theological analysis of the role of preaching within the Christian Brethren Church - Vos, C.J.A. (Casparus Johannes Adam), 1945- (University of Pretoria, 2013)
Dissertation (MA (Theology) : Practical Theology)--University of Pretoria, 2008.